Control interno de los procesos contables del Comercial Ileana Villalba de la ciudad de Babahoyo - Jordán Morán, Rosa Mariela (2021)
His investigation was carried out in the commercial "Ileana Villalba" to find out if they use an accounting system, it was identified that the commercial does not have an internal control of the accounting processes, which has triggered several problems. In the development, it will be possible to observe the importance of having internal control, in the organizational or business structures, and how a work environment is managed if the salesperson had both rules and policies, and how necessary it is to be updated, and have technological equipment efficient to help provide accurate and reliable financial information. Among the techniques used in the case study, an interview was carried out with the owner of the commercial in order to have a direct observation of what affects it, and also obtain information on the internal controls and accounting processes that they use and how they manage their accounting.